Acute-Stress Biomarkers in Three Octopodidae Species After Bottom Trawling - Barragán-Méndez, Cristina; Sobrino, Ignacio; Marín-Rincón, Adrián; Fernández-Boo, Sergio; Costas, Benjamin; Mancera, Juan Miguel; Ruiz-Jarabo, Ignacio (Frontiers in Physiology, 2019)
Several Octopodidae species have a great potential for the diversification of worldwide aquaculture. Unfortunately, the lack of stress-related biomarkers in this taxon results an obstacle for its maintenance in conditions where animal welfare is of paramount relevance. In this study, we made a first approach to uncover physiological responses related to fishing capture in Eledone moschata, E. cirrhosa and Octopus vulgaris. Captured octopus from all three species were individually maintained in an aquaculture system onboard of oceanographic vessel in south-western waters of Europe. Haemolymph plasma and muscle were collected in animals at the moment of capture, and recovery was evaluated along a time-course of 48 h in Eledone spp., and 24 h for O. vulgaris. Survival rates of these species captured in spring and autumn were evaluated. Physiological parameters such as plasma pH, total CO2, peroxidase activity, lysozyme, hemocyanin, proteases, pro-phenoloxidase, anti-proteases, free amino acids, lactate and glucose levels, as well as muscle water percentage, free amino acids, lactate, glycogen and glucose values were analysed. The immune system appears to be compromised in these species due to capture processes, while energy metabolites were mobilized to face the acute-stress situation, but recovery of all described parameters occurs within the first 24 h after capture. Moreover, this situation exerts hydric balance changes, as observed in the muscle water, being these responses depending on the species assessed. In conclusion, three Octopodidae species from south-western waters of Europe have been evaluated for stress-related biomarkers resulting in differentiated mechanisms between species. This study may pave the way to further study the physiology of stress in adult octopuses and develop new methodologies for their growth in aquaculture conditions.